Heat Stress Causes Immune Abnormalities via Massive Damage to Effect Proliferation and Differentiation of Lymphocytes in Broiler Chickens - Hirakawa, Ryota; Nurjanah, Siti; Furukawa, Kyohei; Murai, Atsushi; Kikusato, Motoi; Nochi, Tomonori; Toyomizu, Masaaki (Frontiers in Veterinary Science, 2020)
Broiler chickens are highly sensitive to high ambient temperatures due to their feathers, lack of skin sweat glands, and high productivity. Heat stress (HS) is a major concern for the poultry industry because it negatively affects growth as well as immune functions, which increase the potential risk of infectious disease outbreaks. Therefore, it is vital to elucidate HS’s effect on the avian immune system, especially considering the global rise in average surface temperature. Our study identified a series of immunological disorders in heat-stressed broiler chickens. We exposed 22-day-old broiler chickens to a continuous HS condition (34.5 ± 0.5º C) for 14 days and immunized them with a prototype bovine serum albumin (BSA) antigen. The plasma and lymphoid tissues (thymus, bursa of Fabricius, and spleen) were harvested at the end of the experiments to investigate the induction of BSA-specific immune responses. Our results revealed that plasma titers of immunoglobulin (Ig)Y, IgM, and IgA antibodies specific for BSA were lower than those of thermoneutral chickens immunized with BSA. Furthermore, the spleens of the heat-stressed broiler chickens displayed severe depression of Bu1+ B cells and CD3+ T cells, including CD4+ T cells and CD8+ T cells, and lacked a fully developed germinal center (GC), which is crucial for B cell proliferation. These immunological abnormalities might be associated with severe depression of CD4−CD8− or CD4+CD8+ cells, which are precursors of either helper or killer T cells in the thymus and Bu1+ B cells in the bursa of Fabricius. Importantly, HS severely damaged the morphology of the thymic cortex and bursal follicles, where functional maturation of T and B cells occur. These results indicate that HS causes multiple immune abnormalities in broiler chickens by impairing the developmental process and functional maturation of T and B cells in both primary and secondary lymphoid tissues.